Booster COVID-19 mRNA vaccination ameliorates impaired B-cell but not T-cell responses in older adults - Kometani, Kohei; Yorimitsu, Takaaki; Jo, Norihide; Yamaguchi, Erina; Kikuchi, Osamu; Fukahori, Masaru; Sawada, Takeshi; Tsujimoto, Yoshitaka; Sunami, Ayana; Li, Mengqian; Ito, Takeshi; Pretemer, Yann; et al. (Frontiers in Immunology, 2024)
Age-associated differences in the effect of repetitive vaccination, particularly on memory T-cell and B-cell responses, remain unclear. While older adults (aged ≥65 years) exhibited enhanced IgG responses following COVID-19 mRNA booster vaccination, they produced fewer spike-specific circulating follicular helper T cells-1 than younger adults. Similarly, the cytotoxic CD8+ T-cell response remained diminished with reduced PD-1 expression even after booster vaccination compared with that in younger adults, suggesting impaired memory T-cell activation in older adults. In contrast, although B-cell responses in older adults were weaker than those in younger adults in the primary response, the responses were significantly enhanced upon booster vaccination, reaching levels comparable with that observed in younger adults. Therefore, while booster vaccination ameliorates impaired humoral immunity in older adults by efficiently stimulating memory B-cell responses, it may less effectively enhance T-cell-mediated cellular immunity. Our study provides insights for the development of effective therapeutic and vaccine strategies for the most vulnerable older population.